2006
DOI: 10.1097/01.aud.0000240507.83072.e7
|View full text |Cite
|
Sign up to set email alerts
|

Olivocochlear Efferents: Anatomy, Physiology, Function, and the Measurement of Efferent Effects in Humans

Abstract: This review covers the basic anatomy and physiology of the olivocochlear reflexes and the use of otoacoustic emissions (OAEs) in humans to monitor the effects of one group, the medial olivocochlear (MOC) efferents. MOC fibers synapse on outer hair cells (OHCs), and activation of these fibers inhibits basilar membrane responses to low-level sounds. This MOC-induced decrease in the gain of the cochlear amplifier is reflected in changes in OAEs. Any OAE can be used to monitor MOC effects on the cochlear amplifier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
563
3
47

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 560 publications
(622 citation statements)
references
References 128 publications
9
563
3
47
Order By: Relevance
“…The main role of MOC efferents in everyday hearing is thought to be to reduce masking (Guinan 2006). The narrow MOC-fiber TCs and the MOC cochlear innervation pattern have suggested that the MOC reflex provides frequency-specific antimasking (Winslow and Sachs 1987).…”
Section: Implications Of the Results For The Role Of Moc Efferents Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The main role of MOC efferents in everyday hearing is thought to be to reduce masking (Guinan 2006). The narrow MOC-fiber TCs and the MOC cochlear innervation pattern have suggested that the MOC reflex provides frequency-specific antimasking (Winslow and Sachs 1987).…”
Section: Implications Of the Results For The Role Of Moc Efferents Inmentioning
confidence: 99%
“…This tone completely suppressed the probefrequency SFOAE, with the result that only MEM contractions could produce a change in the sound pressure at the SFOAE probe frequency. Thus, the presence of an elicitor-induced change in the earcanal sound at the SFOAE frequency indicates there has been a MEM contraction, while responses within the noise floor are taken to mean there has been no significant MEM contraction (see Guinan 2006).…”
Section: Middle Ear Muscle Contraction Testmentioning
confidence: 99%
“…Few studies have used this approach, and they report greater effects in the tails than in the tips of the PTCs (Kawase et al 2000;Quaranta et al 2005;Vinay and Moore 2008). At first sight, this appears inconsistent with the wellestablished physiological evidence that efferent activation affects mostly the tip of basal BM tuning curves, that is, the stimulus frequencies subject to cochlear compression (Guinan 2006(Guinan , 2010. This inconsistency, however, is likely more apparent than real as, in contrast to BM tuning curves, two stimuli are required to measure a PTC (a probe tone and a masker sound) and so efferents may affect either or both of them.…”
Section: Introductionmentioning
confidence: 97%
“…Medial olivocochlear (MOC) efferent neurons innervate these cells and convey signals that are capable of controlling BM sensitivity and tuning (Murugasu and Russell 1996;Russell and Murugasu 1997;Cooper and Guinan 2006). MOC efferents may be activated in a reflexive manner by contralateral sounds (Guinan 2006(Guinan , 2010. Therefore, cochlear responses may change dynamically in binaural listening situations.…”
Section: Introductionmentioning
confidence: 99%
“…The apparent discrimination deficits in the dichotic s/n condition could, at least partly, be explained by the influence of the subcortical efferent central auditory system, more specifically the medial olivocochlear bundle (MOCB; see Guinan 2006 for an overview). The function of the MOCB can be investigated by measuring otoacoustic emissions (OAE).…”
Section: Discrimination Deficits and Possible Top-down Engagementmentioning
confidence: 99%